A bibliometric analysis of E-Democracy on government research - Danang Eko Prastya; Misran; Achmad Nurmandi (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2021)
ABSTRACTThis study aims to determine the development of research with the theme E-Democracy on Government in the last ten years from 2011 to 2020. The research method uses qualitative research with literature review or literature review. Data were collected by accessing journals on Scopus and obtaining 120 high-citation articles with ten years from 2010 to 2020. Data analysis used the Vosviewer and Nvivo 12 Plus applications. The results showed that 120 journals studied E-Democracy on Government from 2010 to 2020, with the most significant contributor being the United States. Government Information Quarterly is a popular journal with the most discussion on e-democracy. This study's limitation is that the articles reviewed were only obtained from the Scopus database, so they did not have comparable data. Consequently, future studies need to use a comparative analytical approach involving the Scopus database and the Web of Sciences (WoS). ABSTRAKAnalisis Bibliometrik E-Demokrasi pada Riset Pemerintah. Penelitian ini bertujuan untuk mengetahui perkembangan penelitian dengan tema E-Democracy on Government dalam kurun waktu sepuluh tahun terakhir dari tahun 2011 hingga 2020 .Metode penelitian menggunakan penelitian kualitatif dengan kajian pustaka atau literature review. Data dikumpulkan dengan mengakses jurnal di Scopus dan diperoleh 120 artikel bersitasi tinggi dengan rentang waktu 10 tahun dari 2010 hingga 2020. Analisis data menggunakan aplikasi Vosviewer dan Nvivo 12 Plus. Hasil penelitian menunjukan terdapat 120 jurnal yang mengkaji E-Democracy on Government pada tahun 2010 hingga 2020 dengan negara penyumbang terbesar ialah United States. Government Information Quarterly menjadi jurnal yang populer dengan pembahasan e-demokrasi terbanyak. Keterbatasan dari penelitian ini adalah artikel yang direview hanya diperoleh dari database Scopus sehingga tidak memiliki data pembanding. Akibatnya, studi masa depan perlu menggunakan pendekatan analisis komparatif yang melibatkan database Scopus dan Web of Sciences (WoS)